Posterior fossa ICP monitoring: a tale of two compartments. (4th March 2021) - Khan, Amad; Borg, Nicholas; Shenouda, Emad
Abstract: Aim: Measuring the intracranial pressure (ICP) of the infra-tentorial, posterior fossa compartment has long been avoided due to a lack of precedent and interpretability, as well as concern of damage to the underlying vital structures. In cases of posterior fossa insults however, the supra-tentorial compartment ICPs can be falsely reassuring. We aimed to measure the posterior fossa ICP in such a case and analyse the resulting data. Methods: We present a case of posterior fossa ICP monitoring and discuss its safety profile, rationale and possible indications. Results: Our comparison of the supra and infra-tentorial ICPs showed that there was a statistically significant difference in the two compartments. The infra-tentorial compartment had ICPs averaging 11.02 ± 2.24 mmHg whilst the supra-tentorial compartment averaged 4.94 ± 1.80 mmHg in the first 72 hours post-op (p < .01 on paired t-testing). After 72 hours, the pressures seemed to equilibrate and were 4.71 ± 2.6 and 3.88 ± 2.89 for the infra and supra-tentorial compartments respectively. Conclusion: We propose that where a patient with a posterior fossa insult exhibits signs and symptoms consistent with raised ICP but the supra-tentorial readings are normal, posterior fossa ICP monitoring can be considered.